Analisis dan Perancangan Sistem Pendukung Keputusan Pemberian Bonus Tahunan Karyawan dengan Metode SAW pada PT. XYZ - Triyana Widya Ningrum; Sherly Valentina; Dafid Dafid (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Employees are one of important things in PT. XYZ. Therefore, the company continually give a reward to employee in the form of bonus based on employee performance in order to motivate employee to work harder. PT. XYZ have difficulty to decide who employee that meet the criteria to receive bonus. This research intend to make company easier to select qualified employee to receive annual bonus. Method of collecting data using study of literature, interview and obervation. Methodology of system development is iterative. Method of decision support system using Simple Additive Weighting to select employee that meet the criteria to receive bonus. The system will be develop into employee data, criteria data, calculation of criteria, assesment of employee performance and reporting of selected employee. The result of this research is a design of desicion support system that easir company to decide the bonus receiver’s qualified employee